A study from the perspective of cognitive psychology about the movie “Fun Mind” (Research, Society and Development, 2020)
This paper refers to an analysis of the movie Inside Out (2015) from the point of view of Psychology, in order to highlight the contents studied in the discipline of Basic Processes. It aims to examine the film, highlight its main processes, in order to understand the case and apply it to practice, presenting it in a clinical forum, from the perspective of Cognitivist Psychology. The five methodological steps of the Maguerez Arch were used for the analysis of the film. A bibliographic research was also made, and the t data collection was performed in the electronic databases Electronic Scientific Online Library (Scielo), also bibliographic material found in the university library and the theoretical contents and practical classes treated in class. The results of this research indicate that in all the circumstances experienced, one enjoys various emotions, thus, the film illustrates the main character entering a depressive picture due to the absence of emotions and disharmonious internal processes.Thus, it is concluded that cognitive behavioral therapy would be the best form of treatment, and, in order to have quality of life, all emotions must be balanced.